Trends and disparities in sleep quality and duration in older adults in China from 2008 to 2018: A national observational study - Zihao Tao; Zihao Tao; Yuting Feng; Jue Liu; Liyuan Tao; Liyuan Tao (Frontiers in Public Health, 2023)
BackgroundPoor sleep status as a common concern is a risk factor for many health problems among older people. China with an aging society lacks relevant nationwide data on the sleep status among older people. Therefore, the purpose of this study was to investigate trends and disparities in sleep quality and duration among older adults, and exploring influencing factors of poor sleep in China between 2008 and 2018.MethodWe used the four-waves data of the Chinese Longitudinal Healthy Longevity Survey (CLHLS) from 2008 to 2018. Sleep quality and average sleep hours per day was investigated by using questionnaires in the CLHLS. We categorized sleep duration as three groups including ≤5 h (short duration), 5–9 h (normal duration), or ≥9 h (long duration) per day. Multivariate logistic regression models were used to examine trends and risk factors of poor sleep quality, short sleep duration, and long sleep duration.ResultsThe prevalence of poor sleep quality significantly increased from 34.87% in 2008 to 47.67% in 2018 (p < 0.05). Short sleep duration significantly increased from 5.29 to 8.37%, whereas long sleep duration decreased from 28.77 to 19.27%. Multivariate analysis showed that female sex, poor economic status, a greater number of chronic diseases, underweight, poor self-reported quality of life, and poor self-reported health were associated with poor sleep quality and short sleep duration (p < 0.05).ConclusionOur findings revealed that older adults had increased prevalence of poor sleep quality and short sleep duration from 2008 to 2018. More attention should be paid to the increased sleep problems among older adults and early interventions should be made to improve sleep quality and guarantee enough sleep time.